Effect of using protocols on medical care: randomised trial of three methods of taking an antenatal history. Issue 6863 (14th November 1992) - Lilford, R. J.; Kelly, M.; Baines, A.; Cameron, S.; Cave, M.; Guthrie, K.; Thornton, J.
Abstract : OBJECTIVE--To compare the effectiveness of three methods of taking an antenatal history on the quality of obstetric care. DESIGN--Randomised controlled trial. SETTING--Antenatal clinic of St James's University Hospital, Leeds. SUBJECTS--2424 women attending the hospital for the first (booking) visit. INTERVENTIONS--Histories were taken by midwives using an unstructured paper questionnaire, a structured paper questionnaire (incorporating a checklist), or an interactive computerised questionnaire (incorporating 101 clinical reminders). MAIN OUTCOME MEASURES--The number of clinical responses to factors arising from the antenatal booking history according to method of taking the history. Actions were categorised as medical and surgical, obstetric, personal, current symptoms and treatment, related to maternal age, and related to two common actions (cervical smear testing and dental hygiene) and were weighted for clinical importance by 10 obstetricians. RESULTS--Overall the unstructured questionnaire generated 1063 actions, the structured questionnaire 1146, and the computerised questionnaire 1122. The clinical importance of these actions was lowest for the unstructured questionnaire (overall total value score 1987 v 2182 and 2110 for the structured and computerised questionnaires respectively). The structured questionnaire was better than the computerised questionnaire in the medical and surgical (total value score 191 v 184), obstetric (275 v 241), and personal (430 v 360) categories but inferior in the current symptoms category (179 v 191). CONCLUSION--Structured questionnaires (computerised or paper) provide more and better information, and their use improves clinical response to risk factors. Computerised systems offer no further advantage in antenatal clinics.